Predictors of short-term mortality in HIV-infected patients admitted to Intensive Care Unit - Pereira, Marco Aurélio Bulhões; Nunes, Raphael Pinheiro; Bertelli, Vinicius Thiago Conde; Oliveira, Vanessa Marcon de; Gubert, Vanessa Terezinha; Oliveira, Ana Lúcia Lyrio de (ABCS Health Sciences, 2023)
Introduction: Historically, complications of HIV infection have been related to admissions to the Intensive Care Unit (ICU). Despite therapeutic advances, the results of the analysis of prognostic factors in patients with HIV/AIDS have varied, including late diagnosis and failure to adhere to antiretroviral treatment. Objective: To evaluate the predictors of short-term mortality in HIV-infected patients admitted to the ICU, as well as their sociodemographic and clinical characteristics. Methods: A retrospective cohort study including patients admitted to the ICU of a teaching hospital from 2003 through 2012. Data were collected from medical records after the Institutional Review Board approval. Results: 148 HIV-infected patients were identified and 131 were eligible. Among included patients, 42.75% were HIV new diagnoses and 5.34% had no information about the time of diagnosis. The main reasons for admission to the ICU were respiratory failure and sepsis while mortality was 70.23% between 2003 and 2012. Among the risk factors for mortality were low albumin, high APACHE, low CD4+ T lymphocyte count, and not using antiretroviral therapy. Conclusion: Despite the availability of diagnosis and treatment for HIV-infected individuals, the number of new cases of advanced Aids diagnosed in high-complexity services such as ICU is high, as well as the non-use of combination antiretroviral therapy. It is necessary to strengthen anti-HIV screening to detect and treat more cases in the early stages.